Nonoperative Treatment of Acute Uncomplicated Appendicitis During Pregnancy - Kirkil, Cuneyt; Bozdag, Ahmet; Korkmaz, Mehmet Fatih (Sci Printers & Publ Inc, 2021)
OBJECTIVE: Acute appendicitis (AA) is the most common indication for surgery for nonobstetric conditions during pregnancy. There is a tendency to perform early appendectomy even if there is only a suspicion of AA to avoid the complications of perforation, but negative appendectomies also carry risks of morbidity for both the mother and the fetus. There is an increasing body of evidence suggesting that nonoperative treatment can be a viable option for the management of acute uncomplicated appendicitis (AUA) in the nonpregnant population. Here, we aimed to report the long-term results of nonoperative treatment of AUA during pregnancy. STUDY DESIGN: The medical records of 7 pregnant women with AUA who were managed with antibiotic treatment between 2010 and 2018 were retrospectively analyzed. They were contacted via telephone and queried whether they had experienced any maternal or fetal complications and symptoms such as migratory right iliac fossa pain, anorexia, or nausea/vomiting that could be associated with recurrent AA. RESULTS: The median age was was 24 years (range, 22-29), median gestational age was 14.5 weeks (range, 6-29), median appendix diameter was 8.5 mm (range, 7-9), mean WBC count was 11.1 +/- 2.9 K/mu L (range, 6.0-15.0), and median length of hospitalization was 2 days (range, 1-6). There was no crossover from nonoperative treatment to surgery and no fetal or maternal complication during hospitalization. All pregnancies reached term with delivery of a live, healthy neonate without any maternal complications. One patient (14.3%) underwent appendectomy because of a recurrent AA after 7 months. Others did not experience any recurrence at a mean 23.2 +/- 13.4-month follow-up (range, 7-41). CONCLUSION: Nonoperative treatment of AUA during pregnancy may be possible. Whether it can reduce complications or waste of resources is unclear. Further studies are needed.
Keywords: acute appendicitis; antibiotics; appendectomy; appendicitis; nonoperative treatment; pregnancy; pregnancy complications